Tacrolimus dose requirement based on the CYP3A5 genotype in renal transplant patients - Qu, Lihui (Oncotarget, 2017)
Tacrolimus (FK506) and cyclosporine A (CsA) are widely used to protect graft function after renal transplantation. The aim of the present study is to determine whether the single nucleotide polymorphism of CYP3A5 is a predictive index of FK506 dose requirement, and also the selection yardstick of FK506 or CsA treatment.We tested archival peripheral blood of 218 kidney recipients for CYP3A5 genotyping with PCR-SSP. Meanwhile, the dose of FK506 and CsA was recorded, blood concentration of the drugs was measured, and graft outcome was monitored.These results indicate that CYP3A5*AA/AG carriers need higher FK506 dose than CYP3A5*GG homozygote to achieve the target blood concentration. For CYP3A5*GG carriers, taking FK506 or CsA are both advisable. CYP3A5*AA/AG carriers preferred to CsA treatment depending on the graft outcomes and drug costs. CYP3A5 genotyping is a new approach to detecting FK506 dose requirement and a predictive index for the FK506 or CsA treatment selection in kidney recipients.